Respuesta :

Answer:

The answer to your question is: x = - 14

Step-by-step explanation:

Solve                     4 + x/7 = 2

Multiply by 7     7(4 + x/7 = 2)                

expand             28 + x = 14

simplify             x = 14 - 28

result                 x = - 14

Answer:

A -14

Step-by-step explanation:

I'm going to assume your expression is 4 + (x/7) = 2 as opposed to (4+x) / 7 = 2

4 + (x/7) = 2   (subtract 4 from both sides).

(x/7) = 2 - 4

x/7 = -2  (multiply both sides by 7)

x = -2 (7) = -14

ACCESS MORE